Analysis of the relationship between formula feeding patterns and the risk of early childhood caries through ECC Dentch: Analisis hubungan pola pemberian susu formula dengan risiko kejadian early childhood caries melalui ECC Dentch - Rahmadhani, Triyana Arisfa; Zia, Hanim Khalida; Wisnu, Fredy Rendra Taursia; Iswani, Resti (Makassar Dental Journal PDGI Makassar, 2026)
Dental caries is a health disorder with a high prevalence in all age groups, including infants and children, known as early childhood caries (ECC). One of the most common causes of ECC is the consumption of foods and beverages with high glucose content, including formula milk. This article analyses the rela-tionship between formula milk feeding patterns and the risk of ECC using the ECC Dentch application, which is designed to detect and provide informa-tion related to children's dental health. An analytical survey design was used with a cross-sectional approach on 45 children at Kartika 1-55 Kindergarten in Padang City. Data were obtained through questionnaires and clinical examinations. Although 95.6% of children were at risk of ECC, the chi-square test found no significant relationship between formula feeding patterns and the incidence of ECC (p=0.938). Other factors, such as oral hygiene and consumption of sugary foods, had a more dominant influence on the risk of ECC. The ECC Dentch application was found to have high sensitivity (100%) in detecting cases of ECC, although its specificity was low (0%). It was concluded that there was no significant relationship between formula feeding patterns and the risk of ECC.